Acquiring, Recording, and Analyzing Pathology Data from Experimental Mice: An Overview. Issue 1 (21st March 2014) - Scudamore, Cheryl L.
Abstract: Pathology is often underutilized as an end point in mouse studies in academic research because of a lack of experience and expertise. The use of traditional pathology techniques including necropsy and microscopic analysis can be useful in identifying the basic processes underlying a phenotype and facilitating comparison with equivalent human diseases. This overview aims to provide a guide and reference to the acquisition, recording, and analysis of high‐quality pathology data from experimental mice in an academic research setting. Curr. Protoc. Mouse Biol . 4:1‐10. © 2014 by John Wiley & Sons, Inc.